Public Accountability and Its Impact on Organizational Performance and Public Trus - Tomi Apra Santosa; Sandy Kurniawan; La Ide Zulfikar Hibali (Published by Institut Teknologi Pendidikan Indonesia, 2026)
Public accountability has become a fundamental principle of good governance that enhances organizational effectiveness and strengthens public trust in government institutions. Despite extensive discussions on accountability in the public sector, empirical evidence regarding its simultaneous influence on organizational performance and public trust remains limited, particularly within the context of public service organizations. This study aims to examine the effect of public accountability on organizational performance and public trust. A quantitative explanatory research design was employed using a survey method. Data were collected from 280 respondents consisting of civil servants and public service users selected through stratified random sampling. The research instrument was a structured questionnaire measured using a five-point Likert scale. Data were analyzed using Structural Equation Modeling (SEM) to evaluate both the measurement and structural models. This study concludes that public accountability is a major determinant in improving organizational performance and public trust in public sector organizations. The results of the analysis using PLS-SEM show that public accountability has a positive and significant effect on organizational performance, indicating that the application of the principles of transparency, answerability, responsibility, compliance with regulations, and responsiveness can improve efficiency, effectiveness, service quality, organizational innovation, and public satisfaction. In addition, public accountability is also proven to have a positive and significant effect on public trust, indicating that public organizations that consistently implement an accountability system will gain a higher level of public trust. The findings of this study also prove that organizational performance has a positive and significant effect on public trust, so that the better the organization's performance in providing public services, the stronger the legitimacy and public trust in government institutions.